RESEARCH OF NEUROPROTECTIVE ACTIVITY OF PHYTOREMEDY «PHYTOTON» - T. B. Smagulova; Ya. G. Razuvayeva; S. M. Nikolayev (Acta Biomedica Scientifica, 2012)
The research of neuroprotective activity of phytoremedy «Phytoton» was performed. In experiments on white rats (Wistarline) it was found that «Phytoton» possesses pronounced neuroprotective activity. «Phytoton» reduced. the level of anxiety in animals, attenuated substituting passive defensive reaction, increased orientation and exploratory behavior, and provided nootropic, anxiolytic, antihypoxia action.